Aggressive driving behavior - A review of the literature - Mohd Kassim, Muhammad Asyraf; Abdul Hanan, Suhaila; Aziz, Ahmad Bashir (2018)
Most of the road accident happened in Malaysia involved young driver and motorcyclists.Aggressive behavior on the road has been highlighted as contributing factor of such event.This paper provides a review of current research on young driver behavior, focusing on factors that influence aggressive driving, given that this behavior has received the greatest attention in the young driver literature.The review discusses the concept of aggressive driving, factors influence such behavior and types of aggressive driving that being done by young drivers. In the final section of the paper, recommendations for future research are provided.